Experimental investigation of the consequences of acetylene pressure cylinder failure under fire conditions. (December 2022) - Jankuj, Vojtech; Mynarz, Miroslav; Krietsch, Arne; Spitzer, Stefan H.; Lepik, Petr
Abstract: Acetylene pressure cylinders are widely used in the industrial sector for welding, flame cutting, or heating. Sometimes during work, not only with acetylene cylinders, fires occur and in this case the risk of destruction increases and the behavior of such an exposed cylinder is unpredictable. The purpose of this study is to identify those critical conditions when acetylene cylinders burst and explode in fires. In the present study, acetylene cylinders were exposed to fire conditions. For this purpose, a woodpile as a source of fire was chosen, tested, and evaluated. In addition to the fire condition, this option guaranteed reproducibility and similar conditions for all tests. The individual cylinders were equipped with thermocouples measuring the shell temperature, and half of them were prepared in order to measure the temperatures inside the cylinder. An important factor was the measurement of the amount of pressure that was achieved during the destruction of the cylinder. For this purpose, a pressure transducer was attached to the outlet of the cylinder valve. Exposed to direct fire, they can explode in 10 min, which was confirmed. The critical pressure of 40 bar has been reached in 6 min, followed by destruction after 7 min in fire. Cylinders with internal thermocouples were destroyed when lower pressure was achieved. This confirms the fact that any change of the pressure cylinder affects the original properties. After the tests, the fragments of the selected cylinders were subjected to material tests. The results obtained in these tests are the main source of information for understanding the behavior of acetylene cylinders in fire and the possibility of increasing the safety of intervening rescue services in an emergency. Highlights: Large-scale experiment with acetylene cylinders in fire condition. Destruction of acetylene pressure cylinders. Destruction pressure and temperature of acetylene pressure cylinders. Consequences of acetylene cylinder failure.